INOVASI PEMBELAJARAN BAHASA INDONESIA MELALUI MODEL PROTIGI DAN FROGGY JUMPS: PENINGKATAN CRITICAL THINKING DAN KOMUNIKASI SISWA SEKOLAH DASAR - Muhammad Ali Rahman; Diani Ayu Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problems raised in this study focus on the low critical thinking and communication skills of students. This condition is caused by a learning approach that tends to be one way, lack of active participation from students during the learning process, and students' inability to solve high level thinking (HOTS) questions. To answer these problems, the PROTIGI learning model is applied a combination of Problem Based Learning, Tim Games Tournament, and Group Investigation with the support of Froggy Jumps learning media. The objective of this research is to evaluate the enhancement of students' critical thinking and communication abilities following the application of specific instructional models and media. The study adopts the Classroom Action Research (CAR) approach. The results of the study showed a significant increase: students' critical thinking skills increased from 34% (less skilled category) to 91% (very skilled category) from the first to the fourth meeting. A similar increase also occurred in the aspect of student communication, namely from 43% to 87% in the same period. The findings suggest that applying the PROTIGI instructional model, in conjunction with Froggy Jumps media, proves to be an effective approach for enhancing students' critical thinking and communication abilities during the learning process.